Nanomaterials: The Size Flexibility of Ferritin Nanocage Opens a New Way to Prepare Nanomaterials (Small 37/2017). Issue 37 (4th October 2017) - Zhang, Shengli; Zang, Jiachen; Chen, Hai; Li, Meiliang; Xu, Chuanshan; Zhao, Guanghua
Abstract : In article number1701045, Guanghua Zhao and co‐workers, report a novel and simple way to encapsulate guest molecules within ferritin nanocages at mild experimental conditions. This strategy will lead to an increase in the use of ferritin in nanotechnology moving away from harsh conditions that can cause damage to protein or guest molecules. This method could be applicable to other shelllike proteins as templates to prepare nanomaterials.